The Business Family as the Business Model of Our Time - James Hoopes (International Journal of Family Business Practices, 2018)
The information technology has reduced the cost of business transactions large managerial corporations are giving way to small family business firms. It is good change because family businesses could not only aim to sustain the family economically but also could aim nurturing children. The role of ethics in family business is has not been studied systematically. This paper has argued that family firms are more socially responsible that non-family firms because family firms are breeding ground for core family values. This paper also argues that business literature should lay emphasis on virtues and character based business in place of value and culture based business. To manage for organizational virtue and character is to treat ethics as an end in itself. To manage by values and characters is to treat ethics as means for some ulterior motive. If employees are told that they should be honest because it pays then profit may trump in case of a conflict. The combination of family virtues and business can make the family busines as moral model  or moral leadership for all types of business in this era of high demands for accountability.